Determinants of banking efficiency : Evidence from mena region - Naglaa Elwy Hafez Elessawy; Osama Abdelkhalek Elansary (Cairo : Naglaa Elwy Hafez Elessawy, 2021)
Purpose: An efficient banking system is vital in MENA to provide the required development in the countries of this region, however, in the last decade banking sector in the region has gone through a lot of financial and political difficulties. The main direction of interest of this research is to extend the existing literature that provides proof about the determinants that impact banking efficiency in MENA to help decision makers in those banks to take the required actions to become more efficient.Design/Methodology/Approach: The researcher presents banks{u2019} risk,macroeconomic factors and country risk factors that affect both cost and profit efficiencies. Stochastic frontier analysis SFA is used in measuring profit and cost efficiencies as well as recognized the correlation between efficiency and banks' risk, macroeconomic and country risk factors.The developed SFA model is used on 116 listed commercial banks in MENA over the period from 2011 to 2017.Findings: Consistent with previous studies, results specify that high z-score and liquidity risk reduce cost efficiency, higher capitalization increases cost efficiency and financial Leverage decreases profit efficiency. Findings also show that high GDP growth rate increases profit efficiency whereas credit risk and bank size don{u2019}t have a significant effect on cost and profit efficiency. Results also indicate the presence of 2the quit life hypothesis3 among the banks of MENA. Finally, results present that economic risk,political risk and debt indicator have a significant impact on both cost and profit efficiencies in the banking sector of MENA
Thesis (Ph.D.) - Cairo University - Faculty of Commerce - Department of Business Administration
Issued also as CD
Keywords: Bank; Cost efficiency; Profit efficiency